2020
DOI: 10.1103/physrevb.101.081108
|View full text |Cite
|
Sign up to set email alerts
|

Indications for Lifshitz transitions in the nodal-line semimetal ZrSiTe induced by interlayer interaction

Abstract: The layered material ZrSiTe is currently extensively investigated as a nodal-line semimetal with Dirac-like band crossings protected by nonsymmorphic symmetry close to the Fermi energy. A recent infrared spectroscopy study on ZrSiTe under external pressure found anomalies in the optical response, providing hints for pressure-induced phase transitions at ≈4.1 and ≈6.5 GPa. By pressuredependent Raman spectroscopy and x-ray diffraction measurements combined with electronic band structure calculations we find indi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 72 publications
1
33
0
Order By: Relevance
“…Therefore, the phase transition is thus governed by this particular hopping. It has been previously reported that an increase of interlayer interactions without breaking any crystal symmetry might be responsible of the appearance of Lifshitz transitions in ZiSiTe 17 . Here we find that pressure changes hopping processes within the same Sn-Ba-Sn layer leading to the appearance of a new topological nodal line, without breaking the PT symmetry responsible of the stability of the nodal lines.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, the phase transition is thus governed by this particular hopping. It has been previously reported that an increase of interlayer interactions without breaking any crystal symmetry might be responsible of the appearance of Lifshitz transitions in ZiSiTe 17 . Here we find that pressure changes hopping processes within the same Sn-Ba-Sn layer leading to the appearance of a new topological nodal line, without breaking the PT symmetry responsible of the stability of the nodal lines.…”
Section: Resultsmentioning
confidence: 98%
“…Raman spectroscopy and X-ray diffraction measurements as well as calculations have found that they correspond to Lifshitz transitions, in which the topology of the Fermi surface changes without breaking any lattice symmetry. Interlayer interactions caused by pressure are found to be responsible of these transitions 17 . However, the topological character of these transitions cannot be elucidated from these experiments.…”
Section: Introductionmentioning
confidence: 96%
“…Its large region of topologically protected drumhead surface states [13] as well as very large spin Berry curvature and associated spin Hall and Nernst response [14] suggest spintronic and related applications. Suggested changes of Fermi surface topology in this family include a temperature-induced Lifshitz transition in ZrSiSe [15], and a pressure-induced Lifshitz transition in ZrSiTe [16] as well as indications of a photoinduced phonon driven transformation [17].…”
mentioning
confidence: 99%
“…DFT calculations were also carried out using the Perdew-Burke-Ernzerhof (PBE) potential [19] as implemented in the WIEN2K code [20]. Experimental structure parameters a = 3.71 Å, c = 9.51 Å, with Zr z = 0.2238 and Te z = 0.6399, were used [16,21,22] with a cutoff parameter k max = 7/R MT inside the interstitial region. A mesh of 3000 k points was employed for the initial calculations.…”
mentioning
confidence: 99%
See 1 more Smart Citation